2018
DOI: 10.1002/alr.22109
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Lund‐Mackay computed tomography score is associated with preoperative symptom severity and predicts quality‐of‐life outcome trajectories after sinus surgery

Abstract: Our study demonstrates that preoperative LMCTS correlate with preoperative extranasal and rhinologic symptom severity and that the LMCTS is an indicator of postsurgical QoL outcomes for medically recalcitrant chronic rhinosinusitis patients in a large tertiary otolaryngology setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
57
1
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 28 publications
7
57
1
5
Order By: Relevance
“…Most previous studies exploring the correlation between the SNOT-22 total score and the Lund–Mackay score have concluded that there is only little correlation [ 15 , 16 ]. However, similar to the present study, Brooks and colleagues observed a significant association between preoperative and postoperative SNOT-22 total scores (both p < 0.01) driven by the “ nasal symptoms ” domain [ 13 ]. In accordance with Sedaghat and co-workers, moreover, a significant correlation was found between the “ nasal symptoms ” domain and the Lund–Mackay score [ 24 ].…”
Section: Discussionsupporting
confidence: 87%
“…Most previous studies exploring the correlation between the SNOT-22 total score and the Lund–Mackay score have concluded that there is only little correlation [ 15 , 16 ]. However, similar to the present study, Brooks and colleagues observed a significant association between preoperative and postoperative SNOT-22 total scores (both p < 0.01) driven by the “ nasal symptoms ” domain [ 13 ]. In accordance with Sedaghat and co-workers, moreover, a significant correlation was found between the “ nasal symptoms ” domain and the Lund–Mackay score [ 24 ].…”
Section: Discussionsupporting
confidence: 87%
“…However, truly objective quantification of sinus opacification has been elusive 5 . The well‐known Lund‐Mackay (LM) system 6 provides a simple technique for semiquantitative visual scoring of sinus CT that correlates with clinical measures of disease severity, 7‐9 but does not consistently correlate with symptoms 10 . Visual scoring is also time‐consuming, subjective, and lacks sensitivity to change.…”
mentioning
confidence: 99%
“…The score also correlated with symptom reduction (coeff=0.24, p=0.02), complication rate (OR 1.08, 95% confidence interval (CI) 1.06-1.1) and revision rates (OR 1.03, 95% CI 1.001-1.06) but showed no correlation with SNOT-22 scores. In contrast, a more recent study (220) showed that the preoperative LMS in 665 patients with medically recalcitrant CRS correlated significantly with preoperative extranasal and rhinologic symptom severity on the SNOT-22 and that the LMS was an indicator of postsurgical QOL outcomes.…”
Section: Discussionmentioning
confidence: 74%